Investigation of STEM Subject and Career Aspirations of Lower Secondary School Students in the North Calotte Region of Finland, Norway, and Russia - Päivi Tomperi; Mona Kvivesen; Saeed Manshadi; Stig Uteng; Yulia Shestova; Oleg Lyash; Irina Lazareva; Asya Lyash (MDPI AG, 2022)
This study investigates the suitability of the STEM Career Interest Survey (STEM-CIS) to measure secondary school students' aspirations towards STEM subjects and careers. A confirmatory factor analysis (CFA) was conducted to assess the initial structural validity of the adapted STEM-CIS survey, where the science subscale was extended to four science disciplines, to align with the way science is taught in Finland and Russia. The results indicate that the interest in STEM subjects in general is not at a high level in any of the countries. There is a traditional gender gap regarding STEM subjects in every dimension, which favors females in biology and males in technology and engineering. STEM stereotypes among students-due to low exposure to STEM professions at school-can explain students' low interest despite high self-efficacies. Our study shows that we must increase informal learning opportunities inside and outside school and improve career counselling for students so that they will be more informed of STEM career opportunities.